Restriction spectrum imaging of white matter and its relation to neurological disability in multiple sclerosis. (April 2019) - Sowa, Piotr; Harbo, Hanne F; White, Nathan S; Celius, Elisabeth G; Bartsch, Hauke; Berg-Hansen, Pål; Moen, Stine M; Bjørnerud, Atle; Westlye, Lars T; Andreassen, Ole A; Dale, Anders M; Beyer, Mona K
Background: Restriction spectrum imaging (RSI) is a recently introduced magnetic resonance imaging diffusion technique. The utility of RSI in multiple sclerosis (MS) is unknown. Objective: To investigate the association between RSI-derived parameters and neurological disability in MS. Methods: Seventy-seven relapsing–remitting MS patients were scanned with RSI on a 3-T scanner. RSI-derived parameters: fast and slow apparent diffusion coefficient (sADC), fractional anisotropy, restricted fractional anisotropy, neurite density (ND), cellularity, extracellular water fraction, and free water fraction, were obtained in white matter lesions (WML) and normal appearing white matter (NAWM). Patients were divided into three groups according to their expanded disability status scale (EDSS): with minimal, low, and substantial disability (<2.5, 2.5–3, and >3, respectively). Group comparisons and correlation analyses were performed. Results: All tested RSI-derived parameters differed between WML and NAWM ( p  < 0.001 for all pairwise comparisons). The sADC in WML showed largest difference across disability subgroups (analysis of variance (ANOVA): F  = 5.1, η 2  = 0.12, p  = 0.008). ND in NAWM showed strongest correlation with disability (ϱ = –0.39, p  < 0.001). Conclusion: The strongest correlation with EDSS of ND obtained in NAWM indicates that processes outside lesions are important for disability in MS. Our study suggests that RSI-derived parameters may help understand the "clinico-radiological paradox" and improve disease monitoring in MS.